Students and family functioning during the COVID 19 pandemic - Keskinova, Angelka; Radulovikj, Makedonka; Avirovikj Bundalevska, Irena (Faculty for Special Education and Rehabilitation, University of Tuzla, 2021)
From March 2020, the Republic of North Macedonia started with the implementation of several restrictive measures to protect public health due to the fast and uncontrolled spreading of the coronavirus – COVID 19. As one of the restrictive measures all Macedonian universities were closed on March 11th, followed by quarantine measures which led to a general closure of almost all public businesses and work activities. In early 2021, the pandemic is ongoing and impacts are likely to be longstanding. One of the areas most affected by the pandemic is family functioning, family routines and rituals. Previous studies have confirmed that when students are not in school/university, they are less physically active, have poorer sleep hygiene, and spend more screen time. New family dynamic increased parents’ demands on flexibility to new routines, rules, and limits. The aim of our research was to explore how students experienced their family functioning during the pandemic. The research lasted two months and it was conducted on a sample of 234 university students (197 females and 37 males) from North Macedonia. In the paper we will present the results of the research, focusing on family support, family communication and problems. Our general outcome showed that despite daily challenges, 42% of the respondents rated family communication as excellent, with only 8% of them facing significant problems. We conclude that students in general, during the first pandemic months, adequately deals with everyday family challenges.
Keywords: COVID-19 pandemic, family functioning, students, North Macedonia